Single molecule interactions in biological systems - Tessmer, Ingrid (2003)
The interactions of biological molecules are traditionally investigated using ensemble techniques. These provide information on the molecular behaviour based on averaged data resulting from collective ensemble properties. While this has enabled the resolution of structure and function of many proteins and other biomolecules, an understanding of how and why the molecules go about structural changes and modulate inter- and intra-molecular interactions is difficult to gain using these approaches.